The impact of meridian balance method electro-acupuncture treatment on chronic pelvic pain in women: a three-armed randomised controlled feasibility study using a mixed-methods approach. Issue 4 (November 2018) - Chong, Ooi Thye; Critchley, Hilary OD; Williams, Linda J; Haraldsdottir, Erna; Horne, Andrew W; Fallon, Marie
Introduction: Chronic pelvic pain (CPP) is estimated to affect 6%–27% of women worldwide. In the United Kingdom, over 1 million women suffer from CPP and it has been highlighted as a key area of unmet need. Standard treatments are associated with unacceptable side effects. The meridian balance method electro-acupuncture (BMEA), and traditional Chinese medicine health consultation (TCM HC) (BMEA + TCM HC = BMEA treatment) may be an effective adjunct to standard treatment. Aim: The aim of our study was to evaluate the feasibility of a future trial, to determine the effectiveness of the BMEA treatment for CPP in women. The primary objectives were to determine recruitment and retention rates. The secondary objectives were to assess the effectiveness of the BMEA treatment and acceptability of the study's methodology. Methods: Women with CPP were randomised into BMEA treatment (group 1), TCM HC alone (group 2) (each intervention administered twice weekly for 4 weeks) or National Health Service standard care (NHS SC, group 3). Primary outcomes were assessed by the proportion of eligible participants randomised, and the proportion of randomised participants who returned follow-up questionnaires. Interventions were assessed by validated pain/physical/emotional functioning questionnaires at baseline (0), 4, 8 and 12 weeks. Focus groups and semi-structured telephone interviews were embedded in the study. Results: A total of 30 women (51% of those referred) were randomised over 8 months. Retention rates were 80% (95% confidence interval (CI): 74–96), 53% (95% CI: 36–70) and 87% (95% CI: 63–90), in groups 1, 2, and 3, respectively. Qualitative data suggested a favourable trial experience in groups 1 and 3. Discussion: Group 2 retention rate was problematic and has implications for our next trial. Conclusion: Our study suggests that a future trial to determine the effectiveness of BMEA treatment for women with CPP is feasible but with modifications to the study design.